2016
DOI: 10.1016/j.schres.2016.01.020
|View full text |Cite
|
Sign up to set email alerts
|

nAChR dysfunction as a common substrate for schizophrenia and comorbid nicotine addiction: Current trends and perspectives

Abstract: Introduction The prevalence of tobacco use in the population with schizophrenia is enormously high. Moreover, nicotine dependence is found to be associated with symptom severity and poor outcome in patients with schizophrenia. The neurobiological mechanisms that explain schizophrenia-nicotine dependence comorbidity are not known. This study systematically reviews the evidence highlighting the contribution of nicotinic acetylcholine receptors (nAChRs) to nicotine abuse in schizophrenia. Methods Electronic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 274 publications
(306 reference statements)
2
67
0
Order By: Relevance
“…; Parikh et al . ), while both CHRNA7‐ and BDNF‐mutant mice show cognitive inflexibility (Sakata et al . ; Parikh et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Parikh et al . ), while both CHRNA7‐ and BDNF‐mutant mice show cognitive inflexibility (Sakata et al . ; Parikh et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Lewis and Picciotto ; Parikh et al . ). Previous studies have shown reciprocal regulation between acetylcholine and BDNF.…”
mentioning
confidence: 97%
“…In line with this interpretation is the self-medication hypothesis of addiction, which states that one of the major contributors to addiction is the drive to reduce the negative symptoms that arise during drug withdrawal (Khantzian 1985). In support, nicotine has been shown to alleviate cognitive deficits in various mental disorders such as schizophrenia (Adler et al 1993; for review, see Parikh et al 2016) and attention deficit/ hyperactivity disorder (ADHD, Potter and Newhouse 2008; Evans and Drobes 2009; for review, see Kutlu et al 2015b), two populations that show higher rates of smoking (38%-42% of ADHD population, Pomerleau et al 1995;80%-90% in schizophrenia, George and Krystal 2000;de Leon and Diaz 2005). Also in support of the self-medication hypothesis, there is evidence showing that cognitive deficits during nicotine withdrawal predict future relapse to nicotine use (Rukstalis et al 2005;Patterson et al 2010).…”
Section: Nicotinementioning
confidence: 99%
“…There are several possible reasons why people living with severe mental disorders smoke more than those without mental disorders, including: social determinants of health [5,6]; neurobiological links between addiction and mental illness which cause a shared vulnerability [6,7,8,9]; and possibly therapeutic benefits to smoking such as alleviating symptoms of mental illness and side-effects of psychotropic medications, although this is disputed [8,10,11]. …”
Section: Introductionmentioning
confidence: 99%